From Stalemate to Settlement Lessons for Afghanistan from Historical Insurgencies That Have Been Resolved Through Negotiations - Clarke, Colin P. (RAND Corporation, 2014)
A comprehensive review of historical insurgencies that ended in settlement after a military stalemate shows that these negotiations followed a similar path that can be generalized into a "master narrative" of seven steps executed in a common sequence. Such a narrative could help guide and assess the progress of a similar approach to resolving the conflict in Afghanistan as U.S. forces prepare to withdraw.